Kohesi dan Koherensi Dalam Cerpen “Robohnya Surau Kami” Karya A.A. Navis : Penelitian - Yulismarwina Waruwu; Mastawati Ndruru; Noibe Halawa; Imansudi Zega (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to describe the forms of cohesion and coherence in the short story “Robohnya Surau Kami” by A.A. Navis. The research method used is descriptive qualitative method with documentation and literature study techniques. The results show that cohesion is more dominant than coherence. There are 45 cohesion findings, with details of 26 grammatical cohesion (reference, substitution, ellipsis, conjunction) and 19 lexical cohesion (repetition, antonymy, collocation). Meanwhile, there are only 5 forms of coherence, namely 2 additive coherence and 3 causal coherence. This study concludes that cohesion and coherence are very important to build a cohesive and meaningful text in the short story.